DIRECT-READING METHODS DALAM ANALISIS PAJANAN NANOPARTIKEL PADA PERSONAL BREATHING ZONE (PBZ) DI INDONESIA : SYSTEMATIC LITERATURE REVIEW - Anita Maria Magdalena Silaban; Mila Tejamaya (Universitas Pahlawan, 2021)
Measurement of nanoparticles in the personal breathing zone (PBZ) is an effort to assess the risk of nanoparticle exposure in the workplace. Can be done with Direct-Reading as a monitor effort. Indonesia, as one of the countries that also participates in the use of nanotechnology, requires a measurement method that is appropriate to its conditions. Methods: this systematic literature review examines direct-reading methods. Result: two types of instruments were found for direct reading. Results: by conducting an assessment in accordance with the conditions of the Indonesian state, this study recommends Condensation particle counter (CPC) as an instrument that can be used